Meningkatkan Kepercayaan Diri Remaja Desa Bagan Kuala dengan Bimbingan Kelompok - Atika Rahmadani Rahmadani; Nefi Darmayanti Darmayanti; Ashriyah Burdin; Azizah Harahap; Indah Yani (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Personality is a totality of individuals who provide common characteristics with other individuals. Confidence is a person's basic capital in meeting various needs on their own. Self-guided group activities are one of the tools for developing adolescent self-confidence. The research method used in this journal is a literature review study. The students' self-confidence before and after the group guidance was different, that was, they were better and more active. Based on the results of reviews from several journals, it can be concluded that group guidance can increase self-confidence in adolescents. Keywords: Confidence, Group Conseling, Teenager